Spore morphology and wall ultrastructure of Actinostachys pennula (Sw.) Hook. and A. subtrijuga (Mart.) C. Presl. (Schizaeaceae). (2nd October 2018) - Giacosa, Juan P. Ramos; Barakat, María C.
ABSTRACT: Actinostachys is a genus of the Schizaeaceae with two species reported from America: A. pennula and A. subtrijuga . The spores of the two species are studied using light microscopy, scanning electron microscopy and transmission electron microscopy. The spores are monolete, the equatorial diameter is 46–84 μm and the polar diameter is 26–50 μm. In A. pennula the ornamentation of the spores is foveolate and in A. subtrijuga it is striate, composed by parallel ridges separated by ornamented grooves. In both species, the exospore is two-layered and it is the wall that constitutes the ornamentation of the spores. The perispore is two-layered and thin with granules, and covers the outer surfaces of the exospore including the foveolae. On the spore surface of both species, abundant spheroids are observed. The ultrastructural analysis reveals that some of them are spherules and others globules. The studied species can be easily identified by their spores analysed with light microscopy even without prior treatment. We recommend that the spore ornamentation be included in dichotomous keys and descriptions of Actinostachys . The sporoderm ultrastructure of the species is described for the first time. The results contribute to the identification of the species and also may be valuable characters for systematic and phylogenetic purposes.